2019
DOI: 10.1080/15562948.2019.1569744
|View full text |Cite
|
Sign up to set email alerts
|

Urban Congolese Refugees’ Social Capital and Community Resilience During a Period of Political Violence in Kenya: A Qualitative Study

Abstract: Community resilience has been used as a conceptual framework to promote urban refugee protection, integration, and well-being. In the context of this focus on "refugee communities," it is critical to gain a deeper understanding of the ways urban refugee "communities" function. This study explored urban Congolese refugees' use of social capital to promote resilience during a period of political violence in Nairobi, Kenya. Findings illustrate how refugees used social capital across different contexts to access a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
2
16
1
Order By: Relevance
“…Scholarship pertaining to refugees’ resilience has grown in the past decades. Research in this area has conceptualized resilience as protective factors (Carlson et al, 2012), as stemming from “everyday” processes (Lenette et al, 2013), as embedded in social networks (McMichael & Manderson, 2004; Thomas et al, 2011; Tippens, 2020), and as shaped by cultural, social, and physical ecologies (Darychuk & Jackson, 2015; Pulvirenti & Mason, 2011; Tippens, 2017; Yotebieng et al, 2019). Although these highlight the importance of resilience as a lens to view refugees’ positive adaptation in the face of adversity, there are critiques of how this framework has been applied to the study of forced migration.…”
Section: Theoretical Framework: Cultural Bereavement and Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Scholarship pertaining to refugees’ resilience has grown in the past decades. Research in this area has conceptualized resilience as protective factors (Carlson et al, 2012), as stemming from “everyday” processes (Lenette et al, 2013), as embedded in social networks (McMichael & Manderson, 2004; Thomas et al, 2011; Tippens, 2020), and as shaped by cultural, social, and physical ecologies (Darychuk & Jackson, 2015; Pulvirenti & Mason, 2011; Tippens, 2017; Yotebieng et al, 2019). Although these highlight the importance of resilience as a lens to view refugees’ positive adaptation in the face of adversity, there are critiques of how this framework has been applied to the study of forced migration.…”
Section: Theoretical Framework: Cultural Bereavement and Resiliencementioning
confidence: 99%
“…Although these highlight the importance of resilience as a lens to view refugees’ positive adaptation in the face of adversity, there are critiques of how this framework has been applied to the study of forced migration. For example, Tippens (2020) cautioned there is need for nuance when considering refugees’ “community resilience” as refugees often represent groups of individuals and families who are grouped together due to external factors (e.g., forced migration, peripheralized status in first asylum countries, governments’ resettlement priorities). Labeling group-level processes as community resilience without contextualization may unintentionally obscure within-group dynamics.…”
Section: Theoretical Framework: Cultural Bereavement and Resiliencementioning
confidence: 99%
“…Muhwezi and Sam (2004) also found that support from extended families and members of the host community helped refugees adapt to life in Uganda. Congolese refugees residing in Nairobi, Kenya, were shown to rely on strong, in-group relationships for emotional support while leveraging weaker, out-group networks for informational and instrumental support (Tippens 2019). Support-seeking within religious communities has been used by urban refugees in East Africa to obtain emotional support, spiritual guidance, and material assistance (Bernstein and Okello 2007;Tippens 2017).…”
Section: Refugees' Social Support In Urban Contextsmentioning
confidence: 99%
“…Following global patterns, refugees in East Africa are increasingly bypassing or leaving camps for opportunities in cities (Sommers 2001; UNHCR 2018c); however, it is important to note that refugees in many countries in this region are restricted to designated encampment zones (Crisp 2010). Those who live outside of refugee camps are frequently subjected to harassment, xenophobia, and precarious living situations (O'Loghlen and McWilliams 2017;Pavanello et al 2010;Tippens 2017Tippens , 2019. Although young men have traditionally comprised the majority of urban-displaced refugees, increasing numbers of women, children, and older adult refugees reside in urban spaces across the globe (UNHCR 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, young Congolese refugees in Kenia were able to use social resources of well-being to bolster resilience during their displacement (Tippens, 2019).…”
Section: Case Descriptionmentioning
confidence: 99%